IMPROVING THE PERFORMANCE OF PRIMARY HEALTHCARE CENTERS IN SURABAYA: A COMPARISON OF LEADERSHIP STYLE AND VERTICAL DYAD LINKAGE - Danoe Soesanto (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: Leadership style and Vertical Dyad Linkage have a significant influence on organization’s performance, especially public health service providers. Leadership style is one factor that will influence the performance and management of primary healthcare center (PHC).Aim: This study aims to investigate the influence of leadership style and leader-member exchange to the performance of PHC.Methods: The research is an observational study with a cross-sectional design. There were 27 PHCs involved in the study. Each PHC was represented by 11 respondents including the directors, five health program coordinators, and their five members. Data were collected with questionnaires and then analyzed using Multinomial Logistic Regression (α=0.05).Results: The results of the research show that (37.05%) of PHCs use supportive leadership style, and (33.33%) of them use participative leadership style. Most of the Vertical Dyad Linkage of PHC were imbalanced social overinvestment (40.7%), and the work performance showed enough performance (59.3%). Path-Goal leadership had the most influence on the performance of PHC.Conclusions: Excellent performance of PHC is related to achievement-oriented leadership style. Work performance of PHC can be improved by improving real neutral leader-member exchange. Furthermore, identifying employees’ maturity can be chosen as the leadership style. Employees’ self-esteem can be developed to improve the work performance of PHC. Keywords: Leadership style, Vertical Dyad Linkage, Performance of primary healthcare centre.